PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MAKANAN DAN MINUMAN PERIODE 2020-2024 - Putri Apriani; Mardhiyah Hayati; Weny Rosilawati (LPPM STIE Muhammadiah Bandung, 2026)
This study aims to analyze the influence of profitability, solvency, and liquidity on firm value. The independent variables used in this research are Return on Assets (ROA), Debt to Equity Ratio (DER), and Current Ratio (CR), while firm value is measured using the Price to Book Value (PBV). The analysis employs panel data regression with the Fixed Effect Model, selected based on the results of the Chow and Hausman tests. The findings indicate that ROA and DER have a positive and significant effect on firm value, whereas CR has no significant effect. Simultaneously, the three independent variables significantly influence PBV. The coefficient of determination (R²) of 0.877 shows that 87.7% of the variation in firm value can be explained by ROA, DER, and CR.